Analisa dan Perbandingan QoS Jaringan Internet dengan Metode PPPoE, PPTP, dan L2TP pada Implementasi Hotspot RT/RW Net - Christanto, Febrian Wahyu; Aji, Danang Setya (MULTINETICS, 2023)
Abstract -Analyze and compare Quality of Service (QoS) service quality from internet networks using the PPPoE, PPTP, and L2TP methods in the Implementation of RT/RW Net Hotspots. This research was conducted with the aim of identifying the advantages and disadvantages of each method and comparing their performance in the context of RT/RW Net Hotspots. The PPPoE (Point-to-Point Protocol over Ethernet), PPTP (Point-to-Point Tunneling Protocol), and L2TP (Layer 2 Tunneling Protocol) methods are three commonly used methods for managing internet access on Hotspot networks. The analysis was carried out by comparing the QoS parameters, this method obtained Package Loss with the L2TP method with a QoS index value of 0% in the Very Good category. For the average Delay method of 11 ms in the Very Good category, for the Jitter value of the PPPoE method the value of 1 ms is of good value, while for the Trounghput value of the four methods the best value is the PPPoE Server method with an average value of 930 Mbps with the Very Good category . PPPoE as a protocol that has a good level of security and data transfer in testing. The results of this study are expected to provide a better understanding and help decision-making in choosing the performance of the PPPoE, PPTP, and L2TP methods in the context of implementing RT/RW Net Hotspots.